2014
DOI: 10.1007/s12928-014-0296-y
|View full text |Cite
|
Sign up to set email alerts
|

Fenestration using a scoring balloon Scoreflex® as troubleshooting for acute vessel closure due to intramural hematoma complication in percutaneous coronary intervention

Abstract: This case report demonstrated the usefulness of scoring balloon when luminal narrowing occurred after balloon angioplasty in the left circumflex artery due to coronary intramural hematoma. Although a stent was placed, coronary flow was not improved. We intended to make a fenestra between the true lumen and the hematoma using a scoring balloon (Scoreflex® 2.0 × 10 mm, OrbusNeich, Tokyo, Japan) which was dilated in the distal segment of the branch. Angiograms showed restoration of TIMI-3 flow with a long dissect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Most of the time, decisions regarding balloon dilatation of the lesion are based on the discretion of the operator. This condition may sometimes cause vascular dissection, rupture, or ballooning of the false lumen …”
Section: Discussionmentioning
confidence: 99%
“…Most of the time, decisions regarding balloon dilatation of the lesion are based on the discretion of the operator. This condition may sometimes cause vascular dissection, rupture, or ballooning of the false lumen …”
Section: Discussionmentioning
confidence: 99%
“…However, there are some concerns that stenting may cause longitudinal hematoma extension and is associated with an increased rate of restenosis and stent thrombosis [ 3 , 5 ]. Some studies have reported good results for fenestration using cutting balloons [ 6 ], scoring balloons [ 7 ], and stiff guidewires [ 8 ]. Creating a fenestration between the true lumen and the hematoma leads to a reduction in pressure in the intramural hematoma.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a cutting or scoring balloon to fenestrate the intimomedial flap in order to decompress intramural haematomas is an interesting concept, though not free of risk. A few isolated published cases have reported a favourable outcome93 94; however, this kind of evidence is susceptible to selection and/or publication bias.…”
Section: Acute Managementmentioning
confidence: 99%